Efeito de um protocolo de fisioterapia hospitalar sobre a variabilidade da freqüência cardíaca e variáveis hemodinâmicas de pacientes com infarto agudo do miocárdio - Hiss, Michele Daniela Borges dos Santos (Universidade Federal de São Carlos, 2011)
There are very few published studies evaluating the effect of a protocol of graded exercise of short duration, during phase I cardiac rehabilitation (CR) on the cardiac autonomic modulation in patients after acute myocardial infarction (AMI), thus three investigations were undertaken in order to evaluate the safety of the protocol of cardiovascular therapy (CPT) phase I, as well as observing the behavior of heart rate (HR), blood pressure (BP) and autonomic modulation of HR through HR variability (HRV) in time domain (TD) and frequency (DF) in patients undergoing phase I protocol CPT after the 1st AMI. Physical therapy in phase I of the CR can be initiated 12 to 24 hours after AMI, however, it is common to prolonged bed rest due to fears of instability of the patient. So the goal of the 1st study was to evaluate the hemodynamic and autonomic responses to post-AMI patients undergoing day 1 of phase I protocol of CPT, as well as their safety. We studied 51 patients with first AMI uncomplicated, 5511 years, 76% men and submitted to the 1st day of the protocol CPT Stage I, on average, 24 hours after AMI, consisting of 10 minutes of rest before and after exercises, followed by 4 min of breathing exercises and 5 min of dynamic exercise. The results indicate that the exercise was safe because it caused hemodynamic and autonomic modulation in these patients, without causing any medical complications. The 2nd study aimed to characterize the autonomic and hemodynamic responses to CPT in patients with stage I of an AMI. We studied 21 patients with first uncomplicated AMI, age 5212 years, 81% men, six days a progressive exercise program (phase I CPT), consisting of a daily standard protocol (10 min rest in supine position pre-and post-exercise and 4 min of breathing exercises) and a protocol for dynamic graded exercise, progressing to active-assisted movements of the legs in the first days after AMI, even walking in the last days of hospitalization. The protocol applied CPT promoted hemodynamic and autonomic changes during the course of the year, allowing early mobilization of the patient and gradually preparing to return to their activity of daily living after discharge from hospital, without being observed the presence of any sign and / or symptoms of exercise intolerance. The 3rd study was to evaluate the effects of a progressive exercise protocol used in phase I of RCV on HRV at rest in patients after AMI. We studied thirty-seven patients who were admitted to hospital with first uncomplicated AMI. The treated group (TG) (n= 21, age= 52±12 years) conducted a five-day program of progressive exercises during phase I of the RCV, while the control group (CG) (n= 16, age= 54±11 years) had only breathing exercises. The progressive exercise program performed during the first phase of cardiac rehabilitation associated with clinical treatment increased cardiac vagal modulation and reduced cardiac sympathetic modulation in patients after AMI. Overall Conclusion: The results of the three studies suggest that the protocol is safe when applied CPT started after 24 hours of AMI not complicated, and allows early mobilization of patients and gradually prepare them to return their activity of daily living after discharge, without being observed the presence of any sign and / or symptoms of exercise intolerance. In addition the progressive exercise program that compose the physiotherapy intervention associated with clinical treatment caused an increase in cardiac vagal modulation and reduction of cardiac sympathetic modulation at rest in the patients studied.
Keywords: Fisioterapia; Enfarte do miocárdio; Variabilidade da frequência cardíaca; Sistema cardiovascular - doenças - pacientes - reabilitação; Fisioterapia cardiovascular; Acute myocardial infarction; Cardiac rehabilitation phase I; Heart rate variability; Hospital physiotherapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL